2007
DOI: 10.1002/mnfr.200600186
|View full text |Cite
|
Sign up to set email alerts
|

The epidermal growth factor receptor and human topoisomerases represent potential cellular targets of oligomeric procyanidins

Abstract: Oligomeric procyanidins were found to inhibit the protein tyrosine kinase activity of the epidermal growth factor receptor (EGFR). The inhibitory potency was found to increase with the degree of oligomerisation (PA2 > PC1 >> PB1 = PB2 = PB3 = PB4 >> (-)-epicatechin). To address the question whether the interference with the activity of isolated EGFR preparations also plays a role within intact cells, effects on the phosphorylation status of the EGFR, as a measure of its activity, were determined in human colon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 44 publications
(67 reference statements)
3
25
0
Order By: Relevance
“…This observation, together with various studies in vitro and in vivo suggesting that chemopreventive properties mostly act on the intestinal tract [18][19][20][21]23], supports the hypothesis of a favorable effect of proanthocyanidins against colorectal cancer. Moreover, oligomeric procyanidins were found to inhibit the protein tyrosine kinase activity of the epidermal factor receptor, and this activity, together with other antioxidant properties, was found to increase with the degree of oligomerisation in the colon [17,44,45]. This is in line with our observation of a stronger effect against colorectal cancer from the proanthocyanidins with higher degree of polymerization.…”
Section: Discussionsupporting
confidence: 88%
“…This observation, together with various studies in vitro and in vivo suggesting that chemopreventive properties mostly act on the intestinal tract [18][19][20][21]23], supports the hypothesis of a favorable effect of proanthocyanidins against colorectal cancer. Moreover, oligomeric procyanidins were found to inhibit the protein tyrosine kinase activity of the epidermal factor receptor, and this activity, together with other antioxidant properties, was found to increase with the degree of oligomerisation in the colon [17,44,45]. This is in line with our observation of a stronger effect against colorectal cancer from the proanthocyanidins with higher degree of polymerization.…”
Section: Discussionsupporting
confidence: 88%
“…Relative inhibitory activity was primarily related to the number of phenolic hydroxyl groups (galloyl moieties) found in the active structures, with more groups generally conferring increased effect. More recent studies have observed the same trend [ 143 ]. An interesting study has focused on polyphenol structural elements that rules the mechanism by which polyphenols interact with topoisomerase II [ 144 ].…”
Section: Polyphenol Interactions With Biological Proteinssupporting
confidence: 68%
“…In contrast, extracts containing complex polyphenolic mixtures were found to potently affect the topoisomerase activity implicating a contribution of yet unknown constituents, or synergistic or additive effects. One may speculate that oligomeric and/or polymeric procyanidins contained in berries and grapes might have contributed to the modulation of topoisomerase activity by the extracts observed here, because some procyanidins have been previously characterized as topoisomerase inhibitors [12,33,34].…”
Section: S150mentioning
confidence: 97%